Interação e relações sociais em artigos audiovisuais de pesquisa como um gênero multimodal na perspectiva da Análise Crítica de Gênero - Silva, Thales Cardoso da (2015)
According to Fairclough (2003, p. 77), new communication technologies, especially electronic information technologies have significantly increased the possibilities of communication and human interaction. So, the internet and the emergence of new communication technologies can have an influence on discursive genres, leading them to accompany social and technological possibilities, changing and evolving, what can also affect the academic context. In 2006, a journal based on the digital context was founded: JoVE (Journal of Visualized Experiments), adding to scientific publications new semiotic possibilities: the audio and the video. Thus, the main objective of the present study is to verify how articles published on JoVE are configured interpersonally (HALLIDAY, 1994, 2004, 2014; KRESS, van LEEUWEN, 2006), from the perspective of the Critical Genre Analysis (MOTTA-ROTH, 2006, 2008; MOTTA-ROTH; HEBERLE, 2015), adopting procedures and analytical categories that recognize the multimodal nature of the genre. The corpus of the present study comprehends a total of 10 audiovisual research articles published on JoVE. The criteria for selecting the corpus were recency, access and research area: Biology and Medicine. For the analysis of the verbal semiotic component, firstly, the corpus was transcribed. Then, each text had its clauses identified and parceled, in terms of independent and dependent clauses. After that, each clause was classified in terms of mood and speech function. The first step of the analysis of the visual semiotic component was the transcription of the corpus, from moving images to static images, considering the segmentation of the videos in shots (IEDEMA, 2001). Following that, each shot was classified in terms of the systems that realize visual interactive meanings: contact, power, social distance and attitude. Alongside, an analysis of the publication context was guided, based on official documents published on the journal. Verbally, an instructional nature was mapped, by means of three different resources to demanding activities: imperative clauses, interpersonal metaphors and modulation (SILVA, 2015). Visually, it was possible to map that the visual semiotic component tends to present different functions: creating proximity, locating research procedures in terms of space-time and presenting results of the research. Based on the distribution of predominance, it was possible to propose that audiovisual research articles have the following organization: Rationale, Protocols, Representative Results and Final Considerations. The visual-dynamic and verbal-oral semiotic resources exercise equally relevant roles in the realization of the purpose of the genre, having distinct functions and restrictions duo to their nature and what can be more easily conveyed in the capabilities of the semiotic resource. We consider that audiovisual research articles have a great potential to the area of English for Academic Purposes.